Wilsons Disease in a Young Girl with Abnormal Behavior - Amin, R; Hasan, R; Saha, A; Hossain, AR; Kahhar, MA (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Wilson’s disease is an inborn error of copper metabolism caused by a mutation to the copper-transporting gene ATP7B. Epidemiologic clustering of mutations to the ATP7B gene based on ethnicity has been observed. Diagnosis of the condition is made primarily on the basis of clinical findings, presence of the Kayser–Fleischer ring, and biochemical and radiological parameters. The young patient’s usual presentation is through liver involvement. Uncommonly the young group can present with neuropsychiatric manifestation. Behavior disorder like bizarre activity, personality change, affective or schizophrenic presentation may be the initial presentation of Wilson’s disease. Choreoathetoid movement although not common can also be presented in such patient. A young girl with abnormal behavior with atypical presentation was recently observed in one of the medicine unit of Dhaka Medical College. DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9440 JBCPS 2011; 29(3): 170-173